Paddle propulsive force and power balance: a new approach to performance assessment in flatwater kayaking - Romagnoli, C.; Ditroilo, M.; Bonaiuto, V.; Annino, G.; Gatta, G. (Sports Biomechanics, 2022)
This study aims to determine the propulsive force (Fp) and its timing of application during the paddle stroke confirming the dynamic balance between propulsive and drag powers (Pp = Pd) in kayaking performance. Ten male sub-elite paddlers participated in the study. The athletes carried out three trials of 50 m at three different velocity ranges: 2.70 - 3.00 m/ s; 3.01 - 3.50 m/s and 3.51 - 4.00 m/ s. A constant velocity during each trial was maintained and the section between 15 and 40 m of the total pool length was considered for further analysis. Data were collected using the E-kayak system provided of an instrumented paddle and 2D video analysis. It was observed that the propulsive force increases in intensity (up to 90% of the peak force) as the velocity increases. The dynamic balance between Pd and Pp was confirmed with a Bland and Altman plot (estimated bias: 0.2; LoA: 12.8 and 13.3 W). The related comparisons between the power parameters showed no significant difference (p > 0.050) in each of the considered velocity. By applying the dynamic balance theory between Pp = Pd on the data obtained from the interaction among GPS, force on the paddle and 2D video analysis, it is possible to acquire essential information (Fp, Pp) to monitor the flatwater kayaking performance.